Caffeinated Beverage Intake and Serum Caffeine Metabolites and Risk of Pregnancy Loss (OR17-04-19). (13th June 2019) - Purdue-Smithe, Alexandra; Kim, Keewan; Schisterman, Enrique; Schliep, Karen; Perkins, Neil; Sjaarda, Lindsey; Mills, James; Silver, Robert; Andriessen, Victoria; Alkhalaf, Zeina; Radoc, Jeannie; Mumford, Sunni
Abstract: Objectives: The association between caffeine and pregnancy loss remains controversial due to limitations of prior studies such as relying on self-reported intake only, exposure measurement after clinical confirmation of pregnancy, and potential time-varying confounding by nausea/vomiting and lifestyle factors, which may be affected by prior caffeine exposure. Thus, our aim was to evaluate associations of preconception and early pregnancy serum caffeine, paraxanthine, and theobromine, self-reported intake of caffeinated beverages, and risk of pregnancy loss among 1228 reproductive-age women attempting pregnancy in the EAGeR trial during 2007–2011. Methods: We estimated HRs and 95% CIs for any pregnancy loss, hCG loss (prior to ultrasound confirmation), and clinical loss (after ultrasound confirmation) according to caffeinated beverage intake and caffeine biomarkers measured at preconception and the 8 th week of gestation using weighted adjusted Cox proportional hazards models. Results: At preconception, 67%, 28%, and 9% of women reported any intake of caffeinated sodas, coffee, and tea, respectively. Preconception total caffeinated beverage intake of ≥3 vs. 0 cups/day was associated with 85% (95% CI: 1.18, 2.94) higher risk of any pregnancy loss, driven primarily by associations for hCG loss (HR: 2.88 (95% CI: 1.20, 6.91)). Caffeinated soda intake was associated with hCG loss (≥2 vs. <2 cups/day HR: 2.11 (95% CI: 1.14, 3.89)), whereas caffeinated coffee intake was associated with clinical loss (≥2 vs. <2 cups/day HR: 1.27 (95% CI: 1.02, 2.90)). Likewise, any detectable level of serum caffeine (>0.2 vs. ≤0.2 ng/mL) at preconception was strongly associated with hCG loss (HR: 4.51 (95% CI: 1.36, 14.91)). Serum caffeine, paraxanthine, and theobromine measured at the 8th week of gestation were not associated with risk of loss. Conclusions: Collectively, these data suggest that caffeine intake prior to pregnancy may increase risk of pregnancy loss, particularly in early gestation. Funding Sources: Intramural Research Program of the Eunice Kennedy Shriver National Institute of Child Health and Human Development, NIH, Bethesda, MD.